Performance Assessment Task: A Point of Reference for Science Teachers - this Pandemic and Beyond - Sabijon Jr., Ananias C. (Future Science / FSH-PH Publications, 2021)
The pursuit for quality education, including that in the basic education levels, for sustainable development is clearly described in the Education for Sustainable Development (ESD), one of the17 Sustainable Development Goals (SDGs) by the UN. Accordingly, to equip students, with knowledge, skills, attitudes, and values they'll need to face the difficulties along with sustainable development, there is a need to update some processes currently utilized in science teaching and learning. For this reason, alternative activities and assessment methods, like the use of performance task assessment is needed to improve both the quality of teaching and to provide a meaningful learning experience to students. The purpose of this study was to provide relevant information from extant literature and a sample performance task assessment to encourage Science teachers to utilize these information in their classes. To achieve this purpose, significant information about performance task assessment and an original performance task assessment were presented. The use of performance assessment task is one alternative method to develop critical thinking skills, and to provide an education that is truly relevant to every student in the light of today’s challenges, like the pandemic. It could provide authentic and meaningful learning experience to students, and is very relevant in the context of coping with the challenges the science teachers have been facing. With the many pieces of evidence on its effectiveness and positive learning experience by students provided by literature, it is certain that the use of performance assessment task in Science classes cannot be overemphasized.